2014
DOI: 10.1190/int-2013-0114.1
|View full text |Cite
|
Sign up to set email alerts
|

The role of AVO in prospect risk assessment

Abstract: Essentially all companies exploring for oil and gas should perform a risk analysis to understand the uncertainties in their interpretations and to properly value order prospects in a company’s drilling portfolio. For conventional exploration in clastic environments, primarily sands encased in shales, a key component of the risk analysis process is evaluating direct hydrocarbon indicators, which can have a significant impact on the final risk value. We investigate the role AVO plays in the risk assessment proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…It is therefore also important to adequately rate and integrate the qualities of the various geophysical data into the risking process (Forrest et al, 2010). The database, presently consisting of over 360 prospects, contains wells from a variety of AVO classes (Roden et al, 2014) and geographical locations. Classes 3, 2 constitute the bulk of prospects, with a few from class 1 and 4 settings.…”
Section: Hydrocarbon Risk Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore also important to adequately rate and integrate the qualities of the various geophysical data into the risking process (Forrest et al, 2010). The database, presently consisting of over 360 prospects, contains wells from a variety of AVO classes (Roden et al, 2014) and geographical locations. Classes 3, 2 constitute the bulk of prospects, with a few from class 1 and 4 settings.…”
Section: Hydrocarbon Risk Assessmentmentioning
confidence: 99%
“…Amplitude downdip conformance (see Figure 2) and amplitude consistency in the mapped target area were identified to be important attributes across both classes. Similarly, Roden et al (2014) identified the most important AVO characteristics for prospect risk assessment.…”
Section: Introductionmentioning
confidence: 99%
“…By assigning different Vp, Vs, and densities according to different AVO classes, the response for various AVO classes can be regenerated by AVO forward modeling technique. More rigorous modeling could reveal the correct lithology (Roden et al 2014). According to Break et al 2006;Lasitha et al 2019 in the pre-stack domain, the offset or angle is indicative of three important aspects of seismology.…”
Section: Direct Hydrocarbon Indicator and Analysis Of Pre-stack Gathersmentioning
confidence: 99%
“…Fluid discrimination plays an important role in seismic exploration and reservoir description. Qualitative interpretation [1][2][3][4][5][6] and direct quantitative estimation [7][8][9][10][11] for rock properties are two main methods to discriminate different pore-fluid types. However, the qualitative interpretation, such as the bright-spot, dim-spot, and flat-spot techniques, has difficulties in discriminating the geofluid in complicated lithologic reservoirs.…”
Section: Introductionmentioning
confidence: 99%